Penerapan Analisis Studi Kelayakan Bisnis Dilihat Dari Aspek Pemasaran Pada Praktik Pemasaran E-Commerce “Stick Singkong Krispy” - Rita Sri Silvia Pamuji; Dede Susilo HSBW; Muhamad Nizar Pramudita; Enggun Yoga Nugraha (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
Entrepreneurial business opportunities in the food sector are wide open because all humans definitely need food with this promising opportunity, so we plan to design a culinary business